Factors affecting livelihood choices among the brick workers in Nepal - Bajracharya, Sugat B.; Gurung, Kamala; Silpakar, Simran (Frontiers in Sociology, 2025)
The livelihood choices of the brick workers in their source villages in Rolpa, Salyan and Dang are very limited. Livelihood diversification has been a primary choice for the brick workers due to the seasonality of the brick sector. The factors affecting livelihood choices have been assessed using the sustainable livelihood framework. Using a multinomial regression model for a sample of 500 households spread across the 3 study districts, we identify the factors that determine the choice of main source of livelihood options among the brick workers. We find that an increase in household size, land available for cultivation, livestock count, local market access, and education level is associated with a 2, 15, 5, and 26% higher likelihood of workers selecting agriculture as their main source of income, respectively. In addition to this, external shocks, vulnerability, and changes in trends also impact the availability of livelihood options. Most notably, the COVID-19 pandemic has had a profound impact on livelihood choices with a shift from brick work towards agriculture related work because of the lockdowns in effect at the time of the study. Our findings also show that there is a need for enhancement of capacity of brick workers to sustain their livelihoods by improving their ability to diversify their income sources. Therefore, strengthening the income generation options of the brick workers in the source villages is key to enhance livelihood resilience in the long term.